Eneida Tropical : o povo brasileiro como grande narrativa sobre o Brasil - Ávila, Demetrius Ricco (2019)
This work presents an interpretation of Darcy Ribeiro's O Povo Brasileiro, in light of the contributions of Intellectual History. The starting point for the interpretation is the verification of the totalizing proposal of explanation of Brazil presented in this work. Dated in 1995, this proposal brings it closer, in principle, to the interpretations about the country undertaken by the so-called "1930s generation" of Brazilian social thought. In the search of the motivations for this totalizing proposal, the formation of Darcy Ribeiro is analyzed. This analysis encompasses both its academic professionalization in the social sciences in São Paulo in the 1940s, its political militancy in the PCB at the same time, and the affiliation to labor in the late 1950s. It is also analyzed, his intellectual production between this decade and that of 1980, with greater difficulty in the series of Estudos de Antropologia da Civilização, which would have led to the writing of O Povo Brasileiro, after an interregnum of more than twenty years. It is also examined the insertion of Darcy Ribeiro in the 1990s, in order to explore the context of production of O Povo Brasileiro. Not exactly by taking the events of that decade, of international and national order, by themselves. But in Ribeiro's perspective, seeing how he seized them and, thus, demarcated his positions as a senator and intellectual. Therefore, the analysis of O Povo Brasileiro arises from a cross-linking of dimensions external to the text, that is, the author's formation and the context of production, as it is apprehended and meaning. The analytical work, by intertwining these dimensions, reveals how the Darcy Ribeiro confrontations in the 1990s were transposed into the totalizing explanation of the country. In the same way as it allows confronting Darcy Ribeiro with other intellectuals, who would have influenced him, such as of the "1930s generation"; in addition, it insults the O Povo Brasileiro with the Estudos de Antropologia da Civilização, in order to unveil continuities and ruptures between that book and the set of which supposedly would be the last volume. The ruptures between the book and the series, given the distinct contexts of production, are manifested, among others, in the narrative form of the 1995 writing, in contrast to the scientist objectivism imposed on the predecessor volumes. In O Povo Brasileiro, Darcy Ribeiro reaffirms and mobilizes the past due to the demands inherent to that decade, with a view to the justification of the labor political ideology.